2023
DOI: 10.1186/s12874-022-01802-7
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and retention into longitudinal health research from an adolescent perspective: a qualitative study

Abstract: Background High quality longitudinal studies investigating changes in health behaviours over the transition into early adulthood are critical. However, recruiting and retaining adolescents is challenging. This study explored adolescents’ perspectives of signing up to and continuing involvement in a hypothetical longitudinal health research study. Methods Forty-eight individuals (15-20y) participated in nine in-person focus groups about recruitment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Importantly, a systematic review and meta-analysis of retention of adolescents in longitudinal cohort studies found that improved retention was not associated with increasing the number of such enhancing strategies, but instead associated with barrier-reduction strategies (i.e., those reducing participant burden, such as exibility in data collection) (42). A recent qualitative study of adolescent perspectives on engaging in longitudinal health studies found that key factors for continued involvement include user-friendly reporting (such as technology-based assessment and integration of smartphone apps), exible scheduling, and avoiding excessive outreach (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a systematic review and meta-analysis of retention of adolescents in longitudinal cohort studies found that improved retention was not associated with increasing the number of such enhancing strategies, but instead associated with barrier-reduction strategies (i.e., those reducing participant burden, such as exibility in data collection) (42). A recent qualitative study of adolescent perspectives on engaging in longitudinal health studies found that key factors for continued involvement include user-friendly reporting (such as technology-based assessment and integration of smartphone apps), exible scheduling, and avoiding excessive outreach (43).…”
Section: Discussionmentioning
confidence: 99%
“…Although our study did meet the recruitment rate criteria of 30%, our retention rate fell under 80% and was not su cient to progress to a larger cohort study without further re nement of the study protocol. Our study did incorporate many of the suggestions for effective research engagement set forth in previous studies, such as app-based data collection, offering of nancial incentives, and leveraging pre-existing subject relationships with the research team and/or healthcare institution (43). However, the persistent di culties in subject retention suggest that there were additional barriers to participation.…”
Section: Discussionmentioning
confidence: 99%
“…After extracting a group of users that reported being in the correct age range of [13][14][15][16][17][18][19][20][21][22][23][24][25],…”
Section: Detection Of Sad Diagnosis With Different Levels Of Certaintymentioning
confidence: 99%
“…These studies suffer from known limitations such as reporting bias 19 , recall bias 20 , negativity bias 21 and post-event processing issues 22 . While there have been studies focused on getting information directly from adolescent patients 23,9 , obtaining clinically relevant insights from adolescents, such as patient-reported outcomes, is complicated by challenges with recruitment and patient retention 24 . Best practices for adolescent recruitment emphasize the need to employ a wide variety of recruitment methods, such as text messages, social media, and word of mouth 25 , and a focused and judicious strategy to reduce the participant's burdens 26 to maximize cohort retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation